Identifying the mechanical properties and surface morphology of artocarpus elasticus fiber biocomposites due to the effect of alkali treatment for automotive applications - Mulyanto, Tri; Syamani, Firda Aulya; Ismadi, Ismadi; Purnomo, Deni; Nurjanah, Mona; Setyadi, Iman; Abdillah, Abdul Azis; Permana, Sulaksana (Eastern-European Journal of Enterprise Technologies, 2025)
Lantung bark (Artocarpus elasticus), a natural fiber abundant in Bengkulu and other Indonesian regions, was studied as reinforcement in polyester-based biocomposites. The increasing demand for environmentally friendly materials has driven the development of natural fiber-based biocomposites as alternatives to synthetic materials. The main problem addressed is the weak interfacial bonding between untreated Lantung fibers and polymer matrices, reducing composite mechanical performance. To overcome this, fibers were treated with Sodium Hydroxide (NaOH) solutions at 2%, 4%, and 6% concentrations for 2 hours to improve surface morphology and chemical reactivity. After drying, treated fibers were fabricated into biocomposites using the hand lay-up pressing method. Testing included morphological observation via 3D microscopy and mechanical evaluation through tensile and bending tests based on ASTM standards. Results showed that 2% NaOH treatment provided the best biocomposite’s mechanical properties, with a Modulus of Rupture (MOR) of 82.41 MPa and a Modulus of Elasticity (MOE) of 4.71 GPa. These improvements are explained by effective removal of surface impurities without significant fiber damage, enhancing fiber-matrix adhesion. The distinctive feature of this study is identifying an optimal alkali concentration that maintains fiber integrity while significantly improving mechanical performance. The developed Lantung biocomposites have potential applications as eco-friendly interior or non-structural automotive components requiring moderate tensile strength and high flexural performance